2022
DOI: 10.3389/fmedt.2022.995526
|View full text |Cite
|
Sign up to set email alerts
|

Applications of artificial intelligence in orthopaedic surgery

Abstract: The practice of medicine is rapidly transforming as a result of technological breakthroughs. Artificial intelligence (AI) systems are becoming more and more relevant in medicine and orthopaedic surgery as a result of the nearly exponential growth in computer processing power, cloud based computing, and development, and refining of medical-task specific software algorithms. Because of the extensive role of technologies such as medical imaging that bring high sensitivity, specificity, and positive/negative progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 80 publications
(92 reference statements)
0
18
0
Order By: Relevance
“…Various studies have shown that DL in plain 2D radiographs has comparable accuracy in detecting and classifying fractures when compared to clinicians ( 60 ). Similarly, several ML and AI technologies have been shown to be superior in detecting and staging osteoarthritis of the hip and knee compared to trained radiologists ( 61 ). In addition to that, ML-trained AI programs are better in detecting implant loosening on 2D radiographs than experienced orthopaedic surgeons and can identify the type of implant satisfactory ( 61 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Various studies have shown that DL in plain 2D radiographs has comparable accuracy in detecting and classifying fractures when compared to clinicians ( 60 ). Similarly, several ML and AI technologies have been shown to be superior in detecting and staging osteoarthritis of the hip and knee compared to trained radiologists ( 61 ). In addition to that, ML-trained AI programs are better in detecting implant loosening on 2D radiographs than experienced orthopaedic surgeons and can identify the type of implant satisfactory ( 61 ).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, several ML and AI technologies have been shown to be superior in detecting and staging osteoarthritis of the hip and knee compared to trained radiologists ( 61 ). In addition to that, ML-trained AI programs are better in detecting implant loosening on 2D radiographs than experienced orthopaedic surgeons and can identify the type of implant satisfactory ( 61 ). The automated detection of spinal pathologies using ML-systems also shows good specificity and sensitivity ( 61 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…ANNs have made notable advancements within the field of orthopedic surgery. A recent review [ 24 ] explored their applications across five key orthopedic disciplines: joint reconstruction, spine, orthopedic oncology, trauma, and sports medicine. This review underscores the distinct advantages these algorithms bring in handling and interpreting intricate patient-specific data.…”
Section: Introductionmentioning
confidence: 99%
“…AI and data analytics are revolutionizing orthopedics by enabling predictive and personalized care. AI algorithms can analyze large datasets of patient information to identify trends and predict outcomes [ 6 ]. For example, they can help orthopedic surgeons predict the success of joint replacements or estimate the risk of complications in specific patient populations.…”
Section: Introductionmentioning
confidence: 99%